2005
DOI: 10.1002/zaac.200500152
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I) Chloride Cluster Complexes with Pentaphenyl‐Cyclopentaphosphane as Ligand

Abstract: Pentaphenylcyclopentaphosphane, c-(P 5 Ph 5 ) is conviently prepared from PhPCl 2 and thermally activated zinc powder in thf. Hydrolysis of c-(P 5 Ph 5 ) in the presence of ZnCl 2 gives to an equimolar distribution of PhPH 2 , PhP(ϭO)H 2 , and PhP(ϭO)(OH)H.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Reduction of PhPCl 2 with thermally activated zinc powder in THF and subsequent recrystallization from CH 3 CN afforded pure (PPh) 5 in > 90 % yield. [ 26 ] This improves the known reductions with Li, Na, K or Mg, which give a broader product distribution of (PPh) n ( n = 4, 5, 6). [ 29 ]…”
Section: Synthesis Of Homoleptic Cyclic Oligophosphanesmentioning
confidence: 59%
See 1 more Smart Citation
“…Reduction of PhPCl 2 with thermally activated zinc powder in THF and subsequent recrystallization from CH 3 CN afforded pure (PPh) 5 in > 90 % yield. [ 26 ] This improves the known reductions with Li, Na, K or Mg, which give a broader product distribution of (PPh) n ( n = 4, 5, 6). [ 29 ]…”
Section: Synthesis Of Homoleptic Cyclic Oligophosphanesmentioning
confidence: 59%
“…To further illustrate the versatility of cyclooligophosphanes as building blocks in the formation of coordination polymers or clusters, Grützmacher and co‐workers showed that treatment of Cu(I)Cl with (PPh) 5 affords depending on the reaction time either tetracopper(I) or hexacopper(I) complexes with two intact (PPh) 5 ligands, respectively (Figure 5, I and II). [ 26 ]…”
Section: Reactivity Of Cyclic Oligophosphanesmentioning
confidence: 99%
“…Some of the reaction products that could be identified by NMR spectroscopy are the corresponding imidazole‐2‐thione (IPr)S or imidazole‐2‐selenones (IMes)Se and (IPr)Se,, which indicates lability of the NHC–phosphorus bond. Furthermore, the formation of poly(phenylphosphinidenes) (PPh) n was observed by 31 P NMR spectroscopy during the reaction of 1b with selenium. The reaction of 1c with selenium in C 6 D 6 afforded a greenish solution, with several 31 P NMR spectroscopic signals between 83 and 120 ppm, indicating the formation of (PhP) 3 Se 2 and (PhP) 3 Se 3 (see the Supporting Information) , .…”
Section: Resultsmentioning
confidence: 99%
“…The syntheses that worked best in our hands and gave good yields of pure isolated and crystalline material are outlined in Scheme . In a reductive bond cleavage (RBC) reaction, pentaphenylcyclopentaphosphane ( 1 )2i was treated with an excess of lithium powder in THF. The resulting orange‐red solution showed only one signal at δ =–102.9 ppm in the 31 P NMR spectrum, thus indicating the formation of the P 2 2– dianion.…”
Section: Resultsmentioning
confidence: 99%